PENGARUH PENGGUNAAN MEDIA SIG DENGAN APLIKASI QGIS PADA PEMBELAJARAN GEOGRAFI TERHADAP HASIL BELAJAR SISWA - Nia Kurniati; Budiman Tampubolon; LM. Hari Christanto (Universitas Tanjungpura, 2020)
AbstractThe purpose of this research is to analize the application of Quantum GIS as a learning media in geography learning for the learning outcomes of the X grade student of SMA N 6 Pontianak and also to a also to analize the effect of applying that application. The research approach used a quantitative and an experiment method with quasi experiment form. The population in this research were students in the X grade of SMA N 6 Pontianak 2019/2020 academic year. Data collection used multiple chioce test amounted to 30 questions and data analysis techniques used mann-whitney t-test. The results showed that the average learning outcomes of post-test class experiment is 78,6 and control class is 67,6 gained Zarithmatic > Ztable, is 3,915>1,96, therefore the effect size is 1,04, which is means there is an effect of applying Quantum GIS application for the learning outcomes of the X grade student of SMA N 6 PontianakKeywords: Learning Media, QGIS Application, Learning Outcomes